2019
DOI: 10.3390/su11143912
|View full text |Cite
|
Sign up to set email alerts
|

Human-Leopard (Panthera pardus fusca) Co-Existence in Jhalana Forest Reserve, India

Abstract: The intensity and frequency of human-animal conflicts has escalated in recent decades due to the exponential increase in the human population over the past century and the subsequent encroachment of human activities on wilderness areas. Jhalana Forest Reserve (JFR) presents the characteristics of island biogeography in the heart of Jaipur, which is a city of 3.1 million people. The leopard (Panthera pardus fusca) is the top predator in this newly declared sanctuary of 29 km². We surveyed people in the 18 villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In a 2017 survey of the Reserve we found that leopards used trails and tourist routes for defecation. We monitored the trails, collecting 138 scat samples in the dry season of November 2017–April 2018 (Kumbhojkar et al, 2019; Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2017 survey of the Reserve we found that leopards used trails and tourist routes for defecation. We monitored the trails, collecting 138 scat samples in the dry season of November 2017–April 2018 (Kumbhojkar et al, 2019; Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…We thus hypothesized that the leopards' diet comprises principally of domestic animals. Our objectives were to identify the leopards' key prey species and examine their importance for human–leopard coexistence and acceptance of the presence of leopards in the urban landscape (Kumbhojkar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Locals are unaware of their presence in the close proximity of urban areas because they are nocturnal, secretive and less appealing, making their survival possible in human proximity as long as they have a safe retreat (Gavashelishvili and Lukarevskiy, 2008). In Jhalana Forest Reserve (India), humans and leopards coexist where leopards frequently encounter humans on the forest reserve fringes and in town or villages (Kumbhojkar et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…They are well known among citizens and often serve as a symbol of biodiversity conservation 56 . www.nature.com/scientificreports/ On the other hand, a significant percentage of recorded cases come from urban areas, which may prove that growing anthropopression forces them to coexist with humans 57,58 . Such biases as non-random sampling in online media based studies are expected 33,38 , therefore results should be carefully interpreted.…”
Section: Discussionmentioning
confidence: 99%